Self-Reported Health as Predictor of Allostatic Load and All-Cause Mortality: Findings From the Lolland-Falster Health Study - Neda Esmailzadeh Bruun-Rasmussen; George Napolitano; Stig Egil Bojesen; Stig Egil Bojesen; Christina Ellervik; Christina Ellervik; Christina Ellervik; Knud Rasmussen; Elsebeth Lynge (Frontiers Media S.A., 2024)
Objectives: The aim was to determine the association between self-reported health (SRH), allostatic load (AL) and mortality.Methods: Data derived from the Lolland-Falster Health Study undertaken in Denmark from 2016-2020 (n = 14,104). Median follow-up time for death was 4.6 years where 456 participants died. SRH was assessed with a single question and AL by an index of ten biomarkers. Multinomial regression analysis were used to examine the association between SRH and AL, and Cox regression to explore the association between SRH, AL and mortality.Results: The risk of high AL increased by decreasing level of SRH. The ratio of relative risk (RRR) of having medium vs. low AL was 1.58 (1.11-2.23) in women reporting poor/very poor SRH as compared with very good SRH. For men it was 1.84 (1.20-2.81). For high vs. low AL, the RRR was 2.43 (1.66-3.56) in women and 2.96 (1.87-4.70) in men. The hazard ratio (HR) for all-cause mortality increased by decreasing SRH. For poor/very poor vs. very good SRH, the HR was 6.31 (2.84-13.99) in women and 3.92 (2.12-7.25) in men.Conclusion: Single-item SRH was able to predict risk of high AL and all-cause mortality.